2020
DOI: 10.1142/s0217979220503191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different welding energy on microstructure and toughness of HAZ of low carbon bainitic steel

Abstract: Low carbon bainitic steel (LCBS) with excellent combined properties is the first choice for materials of pipeline transiting geological disaster. However, welding will worsen its toughness. In this paper, three kinds of welding heat input were designed to study the relationship between the toughness and microstructure in the coarse grain zone of welding heat affect zone (CGHAZ) of LCBS. The evolution characteristics of the microstructure of LCBS and the CGHAZ, and impact fracture were investigated by optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The C had no time to diffuse, while the island-shaped carbon-rich austenite was surrounded by the ferrite. They became martensite, and another part remained to form retained austenite [7]. When t 8/5 = 4 s, the cooling rate was fast and the diffusion time of carbon atoms was shorter, so the formed fine carbon-rich austenite region was the granular M-A phase, which was characterized indistinctly.…”
Section: Influence Of M-a Constituents On the Basic Mechanical Proper...mentioning
confidence: 99%
See 1 more Smart Citation
“…The C had no time to diffuse, while the island-shaped carbon-rich austenite was surrounded by the ferrite. They became martensite, and another part remained to form retained austenite [7]. When t 8/5 = 4 s, the cooling rate was fast and the diffusion time of carbon atoms was shorter, so the formed fine carbon-rich austenite region was the granular M-A phase, which was characterized indistinctly.…”
Section: Influence Of M-a Constituents On the Basic Mechanical Proper...mentioning
confidence: 99%
“…However, in the LAHW process of low-carbon bainite steel, the welded joint of the base material (BM) cannot achieve the original mechanical properties attributed to the welding thermal cycle of the heating speed, which is responsible for the characteristics of the local uneven cooling speed. As a result, the HAZ in the joint turns into the main weak area, especially the coarse-grained heat-affected zone (CGHAZ), limiting its application [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…10 The heat-affected zone (HAZ) is considered the weakest zone in joints because of the different phase distribution and chemical components. 11 Wang 12 observed that the heat input during the welding process has a great influence on HAZ toughness. In addition, Vojvodic 13 reported that for high-strength low-alloy steel, the welded joints are critical regions for structural integrity because of the possible brittle fracture behavior.…”
Section: Introductionmentioning
confidence: 99%